Nonlocal boundary-value problems for n-th order ordinary differential equations by matching solutions - Xueyan Liu (Electronic Journal of Differential Equations, 2011)
We are concerned with the existence and uniqueness of solutions to nonlocal boundary-value problems on an interval $[a,c]$ for the differential equation $y^{(n)}=f(x,y,y',dots,y^{(n-1)})$, where $ngeq 3$. We use the method of matching solutions, with some monotonicity conditions on $f$.